2010
DOI: 10.1149/1.3254170
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cathode Inlet Relative Humidity on PEMFC Durability during Startup–Shutdown Cycling

Abstract: This work investigated the effect of cathode inlet relative humidity ͑RH͒ on the durability of proton exchange membrane fuel cells ͑PEMFCs͒ during startup-shutdown cycling via single-cell experiments. Electrochemical techniques, including measurements of polarization curves, electrochemical impedance spectroscopy ͑EIS͒, cyclic voltammetry ͑CV͒, and linear sweep voltammetry, were performed to examine the effect of cathode inlet RH on the degradation of PEMFCs. The performance was better for PEMFCs cycled at a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 22 publications
4
36
0
Order By: Relevance
“…The results of the Petri-Net model using a SSC degradation module was tested using a polarisation curve model as in Figure 9. The model shows a good replication of the polarisation curve drop observed by Kim, et al [19] in Figure 7, with the same logic being carried through the entirety of the Petri-Net model. Each failure mode interaction has a voltage degradation value assigned to it, with some acting reversibly dependent upon the state of the system, and some acting as a counter (irreversible).…”
Section: Verification Of Modelsupporting
confidence: 72%
See 1 more Smart Citation
“…The results of the Petri-Net model using a SSC degradation module was tested using a polarisation curve model as in Figure 9. The model shows a good replication of the polarisation curve drop observed by Kim, et al [19] in Figure 7, with the same logic being carried through the entirety of the Petri-Net model. Each failure mode interaction has a voltage degradation value assigned to it, with some acting reversibly dependent upon the state of the system, and some acting as a counter (irreversible).…”
Section: Verification Of Modelsupporting
confidence: 72%
“…Kim, et al [19] conducted extensive experimentation to reveal the relationship between SSC and degradation of fuel cell performance. Their results show that after 1500 instances of SSC, a drop in performance of 0.08 V was observed (Figure 7).…”
Section: Verification Of Modelmentioning
confidence: 99%
“…The dissolution of Pt particles from the active surface area of the catalyst layer due to the increase in the RH of the reactant gases was reported previously in [245,343]. Uchimura et al [245] found that the active surface area of the catalyst reduces dramatically by around 50% when RH increases from 30 to 100%.…”
Section: Mea and Gdl Structurementioning
confidence: 53%
“…One possible explanation for this is that the high current density they operated at (> 1 A cm -2 ) has generated excessive water facilitating chromium particles to be carried away by the back diffusion stream to the anode. Similarly, the Pt migration detected in [343] was found to be more severe at the cathode layer than the anode. When the cell was operated with three different levels of cathode inlet RH (e.g.…”
Section: Mea and Gdl Structurementioning
confidence: 84%
See 1 more Smart Citation